PENGARUH EKSTERNAL DAN INTERNAL BANK TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Naufal Amiruddin; Khusnul Ashar (Islamic Economics and finance in Focus, 2022)
Islamic banks need to have good performance in order to gain the trust of the public. In assessing the performance of a bank whether it is good or not, it can be seen from its profitability. This study aims to determine the effect of external and internal variables on the profitability of Islamic commercial banks in Indonesia in 2017 - 2019. The external variables consist of GDP and inflation. While the internal variables consist of CAR, NPF and FDR. The analytical method used is multiple linear regression analysis. The results showed that the variables of GDP, inflation, CAR and FDR had no significant effect on the profitability of Islamic commercial banks in Indonesia. While the NPF variable has a significant effect on the profitability of Islamic commercial banks in Indonesia. Future research is expected to be able to add other macroeconomic variables and increase the research period.